Synthesis, in vitro inhibitory activity, kinetic study and molecular docking of novel N-alkyl-deoxynojirimycin derivatives as potential α-glucosidase inhibitors - Ping Lin; Jia-Cheng Zeng; Ji-Guang Chen; Xu-Liang Nie; En Yuan; Xiao-Qiang Wang; Da-Yong Peng; Zhong-Ping Yin (Taylor & Francis Group, 2020)
A series of novel N-alkyl-1-deoxynojirimycin derivatives 25 ∼ 44 were synthesised and evaluated for their in vitro α-glucosidase inhibitory activity to develop α-glucosidase inhibitors with high activity. All twenty compounds exhibited α-glucosidase inhibitory activity with IC50 values ranging from 30.0 ± 0.6 µM to 2000 µM as compared to standard acarbose (IC50 = 822.0 ± 1.5 µM). The most active compound 43 was ∼27-fold more active than acarbose. Kinetic study revealed that compounds 43, 40, and 34 were all competitive inhibitors on α-glucosidase with Ki of 10 µM, 52 µM, and 150 µM, respectively. Molecular docking demonstrated that the high active inhibitors interacted with α-glucosidase by four types of interactions, including hydrogen bonds, π-π stacking interactions, hydrophobic interactions, and electrostatic interaction. Among all the interactions, the π-π stacking interaction and hydrogen bond played a significant role in a various range of activities of the compounds.